Insider threat Prediction Model on Information Leakage in Cloud Computing Environment - Saat, Rozaidah (Institute of Information System & Research Center, 2015)
Cloud computing is a highly- scalable channel that enables the customers to receive IT related services over the internet at a reasonable price. Despite the security concern particularly on information leakage, the convenience and cost effectiveness of this technology with the growing demands for information to be highly integrated and the needs for operational cost reduction makes the adoption of this technology inevitable. As such, risk posed by information leakage will become significant. The solution for information leakage needs to be address proactively by prediction before the incidents. This paper will report the research gaps and work in progress on the evaluations of the Insider threat prediction model to safeguard information security in the context of cloud computing environment.